THE DISCOURSE OF ENVIRONMENTAL AWARENESS IN ENGLISH TEXTBOOKS - Mumtahanah, Andira; Amelia, Dinda (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2025)
This paper investigates the environmental awareness discourse in English textbooks used in Indonesian junior high school education. The primary goal is to evaluate how well this book delivers environmental awareness discourse to 7th grade junior high school pupils. We concentrated our multimodal critical discourse analysis on the topics and discursive capacities of the textbook's texts and visuals. This study investigates the extent to which environmental-related texts inspire profound environmental understanding, using the forms of environmental discourse outlined by Curdt-Christiansen (2021). This study's conclusion emphasizes the importance of increasing environmental understanding among Indonesian students and encouraging healthy environmental behavior. The study's consequences are recommendations for textbook authors (authors and publishers) and textbook users (parents, instructors, and school stakeholders) to critically raise environmental knowledge.